The determinants of customer loyalty towards the Islamic Banking Sector in Johor Bahru, Malaysia. / Aminah Barchot @ Abdul Aziz - Barchot @ Abdul Aziz, Aminah (Faculty of Business and Management, 2019)
This study is conducted due to stiff competition in the banking industry that may influence the growth of Islamic banking system. As the industry become more competitive, the consumers have more choices and change of preference towards Islamic banking. Therefore, this study will determine the factors that influence the customer loyalty on Islamic banking. This will give a solution for Islamic banking sector to maintain and improve their performance by considering the factors in their marketing plans. This study is included five predictor variables which are service quality, product quality, brand image, trust and ability. This study is carried out by taking sample size of 150 participants. The sample that be used is convenience sample, whereby the questionnaires were distributed to any persons that are readily available to answer the questionnaires. The purpose of this study is to determine the factors that can influence the customer loyalty on Islamic banking sector in Johor Bahru, Malaysia. According to the findings of this study, service quality, product quality, trust and ability have significant relationship with the customer loyalty. This research may help the Islamic banking institutions to formulate strategies in order to improve the customer loyalty